IRES special issue. - Worzala, Elaine (Property management, 2002)
The International Real Estate SocietyThat old saying ... Rome was not built in a day ... is a reminder to us all that ittakes time to build anything new and the International Real Estate Society is noexception. However, the papers published in this issue provide strong evidencethat we are well on our way to building an international real estate community.